A descriptive correlation study on students’ satisfaction towards services provided by Universiti Malaysia Kelantan - Mohd Nazri A Rahim, . (2012)
This study aims to understand the students' satisfaction on the services provided by Universiti Malaysia Kelantan. Student satisfaction in this study depends on several factors. Among that factors is the style factor lecturers, facilities provided, organizational culture and the last one is the social environment. The purpose of this study was to examine the level of satisfaction of students of University Malaysia Kelantan. Respondents in this study were UMK students from years 1 to 4 and are divided into three separate campuses of Bachok Campus, Jeli Campus and Campus Pengkalan Chepa . A total of 150 sets of questionnaires were distributed at random in terms of respondents' backgrounds and races as a yardstick to all specified variables. Furthermore, this study uses descriptive analysis, test validity and Pearson correlation as a way to get the results for this study. Based on the results that have been tested, all hypotheses are accepted.